Pineapples in the Eastern Cape : a study of the farm economy and marketing patterns - Strauss, Conrad B (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1961)
The major objective of this study was to seek a better knowledge and greater understanding of the factors associated with successful pineapple farming in the Eastern Cape Region of the Union of South Africa. As no previous Â· investigation equally representative of commercial pineapple farming patterns in the Eastern Cape has been made, this study can be regarded as a pilot survey of the labour structures, rates of production, combination of enterprises; marketing channels and the suitability of various districts in the region of study for the production of pineapples. In addition, the history of the pineapple in South Africa will be traced briefly, and the position the Union holds as a supplier of pineapples on the world market, will be investigated. the importance of the Eastern Cape as a producer of pineapples in South Africa is well known, but is also unequivocally illustrated by the information in Table 1. According to estimates made by the Division of Economics and Markets for 1955/56 season, no less than 86.5 percent of the total acreage planted to pineapples in South Africa, was located in this area. Bathurst, East London and Albany, three of the six districts included in the estimate, were particularly prominent. Taken together, they cultivated more than three-quarters of the total area planted to pineapples in the Eastern Cape, and nearly 70 per cent of the total for South Africa. The remaining quarter of the area cultivated in the Eastern Cape was located in the districts of Peddie, Komgha and Alexandria.
Keywords: Pineapple industry -- South Africa -- Eastern Cape; Agriculture -- Economic aspects -- South Africa; Farm produce -- Marketing